Effect of pyrene substitution on the formation and sensor properties of phthalocyanine-single walled carbon nanotube hybrids - (:unkn) unknown (ELSEVIER SCIENCE SA, 2014)
The hybrids of single walled carbon nanotubes (SWCNTs) with symmetrically octasubstituted zinc phthalocyanine (2) bearing eight polyoxyethylene groups and asymmetrically substituted zinc phthalocyanine (1) bearing one pyrene and six polyoxyethylene groups as side chains have been prepared and characterized by Raman and fluorescence emission spectroscopies, scanning electron and transmission electron (SEM and TEM) microscopies, and thermogravimetric analysis. The pyrene group was chosen to enhance the interaction of phthalocyanine molecules with SWCNTs. Thin films of pristine SWCNTs and SWCNT/ZnPc hybrids were prepared by drop casting onto interdigitated electrodes and employed as active layers to detect ammonia vapour (1-200 ppm) by measuring electrical resistance changes. A comparative analysis of sensors' response of pristine SWCNTs and SWCNT/ZnPc hybrid films to ammonia vapour was carried out to demonstrate the synergic effect between SWCNTs and ZnPc derivatives. Influence of pyrene substituent in the phthalocyanine ring on the hybrid formation and their sensor response has also been discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Carbon nanotubes; Chemical sensors; Ammonia vapour; Conductivity; ZINC PHTHALOCYANINE; GAS SENSOR; NH3; NICKEL; COPPER